A cultural education model: design and implementation of adaptive multimedia interfaces in eLearning - Stewart, Craig (2012)
This thesis presents research performed over the span of 9 years in the area of adaptive multimedia interfaces (specifically Adaptive Hypermedia in eLearning), with special focus on a cultural education model.